2022
DOI: 10.1002/chem.202202194
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of gem‐Difluoro‐ and γ‐Fluoro‐Allyl Boronates and Silanes

Abstract: The electrochemical synthesis of fluorinated allyl silanes and boronates was disclosed. The addition of electrogenerated boryl or silyl radicals onto many α‐trifluoromethyl or α‐difluoromethylstyrenes in an undivided cell allowed the formation of a large panel of synthetically useful gem‐difluoro and γ‐fluoroallyl boronates and silanes (64 examples, from 31 % to 95 % yield). In addition, a scale up of the reactions under continuous flow was showcased using an electrochemical reactor with promising volumetric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Organic electrosynthesis has emerged as an attractive and straightforward approach in dehydrogenation cross-coupling with hydrogen as the only byproduct . Electrochemical generation of silyl radicals has been reported via a stoichiometric NHPI-promoted HAT process and the cleavage of a Si–Cl bond or Si–B bond . However, the silyl radicals are easily further oxidized to silyl cations under electrooxidative conditions, in which the latter can be used to synthesize silanols and silicon-containing cyclic compounds .…”
mentioning
confidence: 99%
“…Organic electrosynthesis has emerged as an attractive and straightforward approach in dehydrogenation cross-coupling with hydrogen as the only byproduct . Electrochemical generation of silyl radicals has been reported via a stoichiometric NHPI-promoted HAT process and the cleavage of a Si–Cl bond or Si–B bond . However, the silyl radicals are easily further oxidized to silyl cations under electrooxidative conditions, in which the latter can be used to synthesize silanols and silicon-containing cyclic compounds .…”
mentioning
confidence: 99%
“…22 The proposed mechanism starts with the oxi- 23 An electrochemical defluoroborylation reaction between α-tri(di)fluoromethyl styrenes and B 2 pin 2 to afford gemdifluoro and γ-fluoroallyl boronate esters was disclosed by Poisson and co-workers (Scheme 9a). 24 This scalable transformation provided an efficient synthetic method for useful fluorinated allyl boronate esters. Very recently, the electrochemical hydroboration of electron-deficient alkenes and allenoates with B 2 pin 2 has also been achieved by the same group (Scheme 9b).…”
Section: Hydroboration Of Unsaturated Compoundsmentioning
confidence: 99%
“…A number of studies have already been reported on the metal‐catalyzed S N 2′ defluoroborylation of fluoroallyl groups using B 2 pin 2 (Scheme 1C) [11] . Recently, an electrochemical method has also been described [12] . Herein, we disclose the first metal‐free defluorinative borylation of 3,3‐difluoropropenes using a combination of B 2 pin 2 and fluoride source to provide β‐boryl‐substituted monofluoroalkenes (Scheme 1D).…”
Section: Introductionmentioning
confidence: 98%